Single cell RNA sequencing reveals molecular and functional platelet bias of aged hematopoietic stem cells - Nerlov, C; Grover, A; Giustacchini, A; Gambardella, A; Macaulay, I; Mead, A; Jacobsen, S; Sanjuan-Pla, A; Thongjuea, S; Carrelha, J; Mancini, E; Luis, T (Nature Publishing Group, 2016)
Aged hematopoietic stem cells (HSCs) generate more myeloid cells and fewer lymphoid cells compared to young HSCs, contributing to decreased adaptive immunity in aged individuals. However, it is not known how intrinsic changes to HSCs and shifts in the balance between biased HSC subsets each contribute to the altered lineage output. Analyzing HSC transcriptomes and HSC function at the single cell level we identify increased molecular platelet priming and functional platelet bias as the predominant age-dependent change to HSCs, including a significant increase in a previously unrecognized class of HSCs that exclusively produce platelets. Depletion of HSC platelet programming through loss of the FOG-1 transcription factor was accompanied by increased lymphoid output. Therefore, increased platelet bias may contribute to the age-associated decrease in lymphopoiesis